The Air Transportation System as a Subsystem of Modern Communication Space: Analysis Based on Transfer Entropy Graphs - Sagit Valeev; Natalya Kondratyeva (Applied Sciences)
The processes of information exchange and the movement of material flows form a communication space that reflects the relationship of complex intersystem interactions in various spheres of our life within the framework of the concepts of information-theoretical theory. One of these concepts, reflecting the mutual influence between processes at a qualitative level, is the transfer of entropy. The direction and intensity of these flows reflect the main social and economic processes. As it is known, air transport is one of the most reliable and high-speed modes of transport, influencing the processes of socio-cultural interaction between different regions. This indirectly affects the development of industrial relations, the development of technology and intercultural exchange. New technologies in aviation improve the flight performance of airliners and reduce the costs of transporting passengers. The size and range of modern airliners are increasing, and ticket prices are being optimized. The processes of the liberalization of developing air transportation markets, the emergence of low-cost air carriers, open skies agreements, and the reduction in restrictions on the nomenclature of carriers and routes have led to the growth and diversity of air transport links. This article considers air transport as a complex system that takes into account the interconnectedness of the elements of the transportation system and the influence of some subsystems on others, which are not always obvious. The object of the study was the communication space formed on the basis of air transportation between regions of the world. To assess the dynamic properties of the world communication space, ICAO data for the period of 1970–2021 were used. The subject of the analysis was a time series reflecting the flows of passengers and cargo over the considered time horizon. The entropy transfer algorithm was used as an analysis tool. In the course of the research, the features of dynamic changes in the properties of the communication space were revealed. The analysis showed that the flows of entropy transfer between regions of the world change depending on political, economic, social, and technological factors. Examples of the application of the proposed approach are considered: an analysis of the cognitive model of the air transport flow structure, an analysis of the regional communication space, and an analysis of changes in the global communication field. The results of the analysis can be useful for assessing the development of the communication field of various regions, which will allow us to solve the problems of forming forecasts and effective scenarios for the development of transport flows at different hierarchical levels of economic management.